The Role of the Principal in Implementing Data-Based Education Planning at Kindergarten - Risdayanti, Fani; Masduki, Masduki; Rahmawati, Desi (research, training and philanthropy institution Natural Aceh, 2025)
This research aims to describe and analyze the principal's experiences implementing data-based educational planning at TK Negeri Sunter Agung, North Jakarta. Data-based education planning is a strategic approach that uses objective data from the Education Report to analyze work programs, annual activity plans, and school activity and budget plans. This study uses a qualitative approach with a case study methodology. Interviews, observations, and document analysis are the data collection techniques used. Data sources consist of primary data (school principal, teachers, school operator, and school committees) and secondary data (educational reports, annual activity plans, school activity and budget plans, curriculum, school profiles, etc.). Research findings indicate that the principal plays a crucial role as a driver of data collection, a leader in implementing data-based educational planning, an empowerer of teachers and academic staff, a collaborator, and an executor of monitoring and evaluation activities.